Characterization of a clinical unit for digital radiography based on irradiation side sampling technology. Issue 10 (10th September 2013) - Rivetti, Stefano; Lanconelli, Nico; Bertolini, Marco; Nitrosi, Andrea; Burani, Aldo
Abstract : Purpose: : A characterization of a clinical unit for digital radiography (FUJIFILM FDR D‐EVO) is presented. This system is based on the irradiation side sampling (ISS) technology and can be equipped with two different scintillators: one traditional gadolinium‐oxysulphide phosphor (GOS) and a needle structured cesium iodide (CsI) phosphor panel. Methods: : The characterization was achieved in terms of response curve, modulation transfer function (MTF), noise power spectra (NPS), detective quantum efficiency (DQE), and psychophysical parameters (contrast‐detail analysis with an automatic reading of CDRAD images). For both scintillation screens the authors accomplished the measurements with four standard beam conditions: RAQ3, RQA5, RQA7, and RQA9. Results: : At the Nyquist frequency (3.33 lp/mm) the MTF is about 35% and 25% for CsI and GOS detectors, respectively. The CsI scintillator has better noise properties than the GOS screen in almost all the conditions. This is particularly true for low‐energy beams, where the noise for the GOS system can go up to a factor 2 greater than that found for CsI. The DQE of the CsI detector reaches a peak of 60%, 60%, 58%, and 50% for the RQA3, RQA5, RQA7, and RQA9 beams, respectively, whereas for the GOS screen the maximum DQE is 40%, 44%, 44%, and 35%. The contrast‐detail analysis confirms that in the majority of cases the CsI scintillator is able to provide improved outcomes to those obtained with the GOS screen. Conclusions: : The limited diffusion of light produced by the ISS reading makes possible the achievement of very good spatial resolution. In fact, the MTF of the unit with the CsI panel is only slightly lower to that achieved with direct conversion detectors. The combination of very good spatial resolution, together with the good noise properties reached with the CsI screen, allows achieving DQE on average about 1.5 times greater than that obtained with GOS. In fact, the DQE of unit equipped with CsI is comparable to the best alternative methods available which are based on the same technology, and similar to others based on an a‐Se direct conversion detectors.